Unification of substantive rules on conformity of goods in private international law - Savanets, Lyudmila (Actual problems of law (Aktual'ni problemi pravoznavstva), 2021)
The unification of substantive rules on the conformity of the goods in private international law is analyzed. The prerequisites for such unification are studied. The concept of conformity of goods, developed by Ernst Rabel on the basis of comparative legal analysis of caveat emptor and caveat venditor in national legal systems, which formed the basis of Article 35 of the UN Convention on Contracts for the International Sale of Goods is investigated. The main idea of the UNIDROIT and UNCITRAL codification works of unification on the international sale of goods was to regulate these relations by the basic principles of private law, formed by a comparative analysis of national laws. The principle of conformity of goods sets out in Article 35 of the UN Convention on Contracts for the International Sale of Goods of 1980 is a legal axiom and an important element of the guarantee of trade.The following conclusions are drawn by the author. Since the twentieth century to the nowadays, the sale contract has been one of the central institutions for the unification of private law at both, universal and regional, international levels. Such legal unification of sale contract contributes to the effectiveness of transnational commercial markets regulation, and also directly affects the improvement of national legislation on sales.The Hague Conventions of 1964: the Uniform Law on the International Sale of Goods and the Uniform Law on the Formation of Contracts for the International Sale of Goods hadn’t got the universal character due to the negligible number of acceded states and didn’t live up to the high expectations of the time. Although only nine countries have ratified the Conventions, seven of which belonged to the then European Economic Community, and only two were not European, their importance for the future unification of private law in the field on sale contracts should not be underestimated.For the first time, unified substantive rules on the conformity of goods with contract were enshrined in the Hague Convention of 1964 the Uniform Law on the International Sale of Goods, where non-conformity was determined through the prism of a seller’s failure to handing over of goods. Subsequently, the Vienna Convention of 1980 established the criteria of non-conformity of goods with the contract, supplemented the requirements for conformity of goods previously established by the Hague Convention of 1964, which concerned the suitability of goods for a particular purpose and packaging. Also, for the first time at the international unified codification level, the Vienna Convention of 1980 regulated the issue of legal defect of the goods as a criterion for its conformity with the contract.The theoretical provisions of the concept of conformity of goods with the contract developed by Professor Ernst Rabel formed the basis of the Hague Convention of 1964 on the Uniform Law on the International Sale of Goods, and later its successor - the Vienna Convention of 1980. Under the influence of the Vienna Convention of 1980 in general, and its article 35, in particular, there have been numerous changes in national legislation, including the formation and development of EU law on sale contract.